DISPROPORTATIONS OF INSTITUTE OF CONTROL OF UKRAINE - Гончарова, М. К.; Субота, А. Г. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The article examines the essence of the concept of state financial control by considering the concepts of “institute of control” – “agent of institute of control” – “subject / quasi-subject of state financial control”, the functioning of agents of institute of control - the Accounting Chamber of Ukraine and the State Audit Service of Ukraine, and the results of their activities on the use of public finance in the framework of official information. The reports of the agents of institute of control were analyzed and conclusions about the continuation of the negative dynamics of illegal and inappropriate use of public resources were made, the spread of budget and financial violations. disproportions that exist in the system of state financial control are identified and ways to eliminate them are defined. The necessity of improvement of functioning of the bodies and the legal mechanism in the management of state financial control in Ukraine is justified, as well as the need to ensure the creation of a unified system of state financial control that is able to resist abuse and prevent possible loss of budget funds by adopting the Code of state financial control of Ukraine, clearly delimiting the powers of internal and external control that could solve such problems as: legal support of control activities and unification of functions and powers of financial control in the executive branch. It is necessary to expand the contents of the basic principles of control in the Budget Code of Ukraine, clearly defining the object and the subject of control, its principles and types, principles of conducting, which will contribute to the expansion of terminology and basic issues of state financial control.